Myocardial hypertrophy, fibrosis and infarction following exposure of the heart to radiation for Hodgkin's disease. Issue 733 (November 1986) - O'Donnell, L.; O'Neill, T.; Toner, M.; O'Briain, S.; Graham, I.
Abstract : A 35 year old man was treated for stage IIA Hodgkin's disease by radiation to the upper thorax, axillae and neck. Three years later he presented with intractable and ultimately fatal congestive heart failure. Autopsy revealed massive biventricular hypertrophy with widespread subendocardial fibrosis and myocardial infarction, but with little coronary artery disease. Such a complex of features has not previously been described after radiation therapy and cannot be adequately explained by other known causes of heart muscle disease. Ventricular hypertrophy with extensive subendocardial fibrosis may be part of the spectrum of radiation heart disease.